Investment Efficiency and the Distribution of Wealth - Banerjee, Abhijit V. (World Bank, Washington, DC, 2017)
The point of departure of this paper is that in the absence of effectively functioning asset markets the distribution of wealth matters for efficiency. Inefficient asset markets depress total factor productivity (TFP) in two ways: first, by not allowing efficient firms to grow to the size that they should achieve (this could include many great firms that are never started); and second, by allowing inefficient firms to survive by depressing the demand for factors (good firms are too small) and hence factor prices. Both of these effects are dampened when the wealth of the economy is in the hands of the most productive people, again, for two reasons: first, because they do not rely as much on asset markets to get outside resources into the firm; and second, because wealth allows them to self insure and therefore they are more willing to take the right amount of risk. None of this, however, tells us that efficiency enhancing redistributions must always be targeted to the poorest. There is some reason to believe that a lot of the inefficiency lies in the fact that many medium size firms are too small.